2020
DOI: 10.5114/pjp.2020.97024
|View full text |Cite
|
Sign up to set email alerts
|

Synovial sarcoma of the stomach: case report and systematic review of the literature

Abstract: Synovial sarcoma is a rare mesenchymal malignant neoplasm that presents a specific t(X;18) translocation forming SS18(SYT)-SSX chimera gene. It is most commonly seen in soft tissues of the extremities. The digestive tract is an exceptional site of involvement. We report a case of primary gastric synovial sarcoma in a 48-year-old female. Differential diagnosis of synovial sarcoma from other spindle cell, mesenchymal and cytokeratin-positive tumors is critical for the treatment and prognosis. Immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…In a previous review of 40 cases of gastric SS, 19 cases were female, the median age was 13-67 years old, the median tumor size was 16-160 mm, the most common histopathological subtype was the monophasic type, more than 50% underwent surgical resection, and less than 25% received adjuvant chemotherapy [ 1 ]. The body of the stomach and fundus are the most common locations, but other locations, such as the gastroesophageal junction, cardia, antrum, and gastroduodenal junction, have also been reported [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous review of 40 cases of gastric SS, 19 cases were female, the median age was 13-67 years old, the median tumor size was 16-160 mm, the most common histopathological subtype was the monophasic type, more than 50% underwent surgical resection, and less than 25% received adjuvant chemotherapy [ 1 ]. The body of the stomach and fundus are the most common locations, but other locations, such as the gastroesophageal junction, cardia, antrum, and gastroduodenal junction, have also been reported [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first case of SS in the stomach was reported in 2000 [ 10 ]. Since then, many cases of SS in the stomach have been reported [ 1 , 2 , 11 - 13 ]. The first reported case of an unusual site of SS in Saudi Arabia was in 2012, arising from the ileum [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 44 cases of primary gastric synovial sarcoma have been reported thus far, and surgical procedures conducted were as follows: tumorectomy in five cases, wedge resection in nine cases, partial gastrectomy in seven cases, gastrectomy in four cases, distal gastrectomy in two cases, total gastrectomy in three cases, antrectomy in one case, intragastric resection in one case, and surgical resection in two cases. No data were available in ten cases [24,[26][27][28][29][30]. Thus, LECS procedure has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…For primary synovial sarcoma of the stomach, Krupinska et al found that patients with tumors larger than 72 mm had a significantly lower probability of survival and that histological subtype could influence the prognosis. In the monophasic subtype group, only one patient died (1/20), whereas in the group with biphasic or poorly differentiated tumors, the percentage of deaths was significantly higher [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, chemotherapy is not recommended for patients with tumors less than 5 cm in diameter and R0 resections [ 30 ]. In the cases of gastric synovial sarcoma, adjuvant chemotherapy was administered in eight patients with tumor diameters of 60 mm or greater [ 5 – 7 , 13 , 20 , 22 , 24 ]. Six of eight patients treated with adjuvant chemotherapy had recurrence, and two of these patients died [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%